The history of Belgium : Part 2. 1815-1865: Waterloo to the death of Leopold I (the end) - Boulger, Demetrius C. (London : D.C. Boulger, 1909)
Bibliotheek Camille Huysmans
Engels
Meerdelige publicatie
Keywords: politieke geschiedenis; België